Evil twins and WPA2 Enterprise: A coming security disaster?. Issue 74 (May 2018) - Bartoli, Alberto; Medvet, Eric; Onesti, Filippo
Abstract: WPA2 Enterprise is a suite of protocols for secure communication in a wireless local network and has become an essential component of virtually every enterprise. In many practical deployments of this technology, a device that authenticates with username and password is at risk of leaking credentials to fraudulent access points claiming to be the enterprise network ( evil twins ) that may be placed virtually anywhere. While this kind of vulnerability is well known to practitioners, we believe these issues deserve a fresh look because the current technological landscape has magnified the corresponding risks. Convergence of organizations toward single sign-on architectures in which a single set of credentials unlock access to all services of the organizations, coupled with the huge diffusion of wifi-enabled personal devices which often contain enterprise credentials and that connect to wifi networks automatically, have made attacks aimed at stealing network credentials particularly attractive to attackers and hard to detect. In this paper we intend to draw the attention of the research and technological community on this important yet, in our opinion, widely underestimated risk. We also suggest a direction for investigating practical solutions able to offer stronger security without requiring any overhaul of existing protocols.